Variation of pore structure in Zhundong coal particle with stepped K2CO3 loading during supercritical water gasification. (1st December 2021) - Zhang, Deming; Wei, Wenwen; Lu, Libo; Jin, Hui; Guo, Liejin
Highlights: The time K2 CO3 promotes the formation of pore structure is during gasification process rather than before gasification. 0 wt%-8 wt% K2 CO3 favors the formation of mesopores and macropores, while 10 wt% K2 CO3 K2 CO3 blocks the pore structure. 0 wt%-4 wt% K2 CO3 loading made pore structure of an ink-bottle type, and 6 wt%-10 wt% K2 CO3 loading made a narrow-slit pore structure. The pore volume has a good linear relationship with carbon gasification efficiency within 8 wt% K2 CO3 loading. Abstract: Supercritical water gasification (SCWG) is a promising technology for coal utilization and has drawn lots of attention. K2 CO3 is an outstanding catalyst for coal gasification and can significantly improve pore structure. The evolution of pore structure in coal particles affects heat and mass transfer efficiency, but little research has investigated the effect of K2 CO3 on gasification results from the perspective of pore structure. Hence, this study revealed the variation of pore structure of coal chars with stepped K2 CO3 loading during SCWG of coal by conducting experiment in a high-capacity autoclave reactor. Gas products and coal chars were characterized by GC, SEM, and BET to obtain the gasification result, surface morphology, and pore structure characteristics of coal chars. The results show that K2 CO3 improved gasification efficiency, gas percentage, and gas yield of H2 and CO2 . The time when K2 CO3 changes pore structure is during the gasification process rather than before gasification. Macropores are dominant in coal chars. 0 wt%-8 wt% K2 CO3 favors the formation of mesopores and macropores, while 10 wt% K2 CO3 blocks the pore structure. 0 wt%-4 wt% K2 CO3 loading makes a pore structure of the ink-bottle type, and 6 wt%-10 wt% K2 CO3 loading makes the narrow-slit pore structure. When K2 CO3 increases from 0 wt% to 8 wt%, production rate of C-containing gases has a good linear relationship with specific surface area, and pore volume also has a good linear relationship with carbon gasification efficiency. 10 wt% K2 CO3 destroys the linear relationship by the blocking effect.